Mycoplasma genitalium protein of adhesion inhibits human urethral epithelial cells apoptosis via CypA/PI3K/AKT/mTOR-dependent autophagy - Chen, Li; Luo, Dan; Xiao, Hua; Zeng, Zhuo; Luo, Haodang; Gao, Siqi; Tang, Xiaoqian; Huang, Zhijia; Zeng, Yanhua (Frontiers in Microbiology, 2025)
BackgroundMycoplasma genitalium, a prokaryotic microorganism, is a known pathogen of sexually transmitted infections. Previously, we identified cyclophilin A (CypA) as the membrane receptor on human urethral epithelial cells (SV-HUC-1) that binds to the M. genitalium protein of adhesion (MgPa) and demonstrated that recombinant MgPa (rMgPa) inhibits apoptosis via CypA-mediated regulation of the PI3K/AKT/NF-κB pathway. Given the established interplay between autophagy and apoptosis, this study aims to investigate whether rMgPa inhibits apoptosis in SV-HUC-1 cells by modulating CypA/PI3K/AKT/mTOR-dependent autophagy.MethodsIn this work, after SV-HUC-1 cells were stimulated with rMgPa, autophagy was detected using Western blotting, immunofluorescence and transmission electron microscopy, respectively. Western blotting and Annexin V/PI assays were used to determine the signaling pathway involved in rMgPa- inhibited apoptosis via inducing autophagy.ResultsrMgPa upregulated the autophagy-related proteins ATG7 and LC3B while downregulating P62 expression in SV-HUC-1 cells. Transmission electron microscopy showed the presence of intracellular autophagosomes, and indirect immunofluorescence confirmed the enhanced expression of LC3B, indicating that rMgPa induces autophagy. Silencing of CypA significantly attenuated rMgPa-induced autophagy, highlighting the essential role of CypA in this process. Furthermore, rMgPa was found to regulate the PI3K/AKT/mTOR pathway via CypA, thereby promoting autophagy. Western blot analysis and Annexin V/PI assays confirmed that rMgPa-induced autophagy inhibits apoptosis in urothelial cells through a CypA-dependent mechanism.ConclusionThis study demonstrates that rMgPa suppresses apoptosis in SV-HUC-1 cells by inducing autophagy via CypA-mediated modulation of the PI3K/AKT/mTOR pathway, which elucidates a novel survival strategy employed by M. genitalium within host cells and provides valuable insights for potential therapeutic interventions targeting M. genitalium infections.